Paediatric snakebite envenoming: recognition and management of cases. Issue 1 (28th October 2020) - Le Geyt, Jacqueline; Pach, Sophie; Gutiérrez, José María; Habib, Abdulrazaq Garba; Maduwage, Kalana Prasad; Hardcastle, Timothy Craig; Hernández Diaz, Roger; Avila-Aguero, María Luisa; Ya, Kyaw Thu; Williams, David; Halbert, Jay
Abstract : Snakebite in children can often be severe or potentially fatal, owing to the lower volume of distribution relative to the amount of venom injected, and there is potential for long-term sequelae. In the second of a two paper series, we describe the pathophysiology of snakebite envenoming including the local and systemic effects. We also describe the diagnosis and management of snakebite envenoming including prehospital first aid and definitive medical and surgical care.